2023
DOI: 10.1038/s41598-023-35811-3
|View full text |Cite
|
Sign up to set email alerts
|

Eribulin inhibits growth of cutaneous squamous cell carcinoma cell lines and a novel patient-derived xenograft

Abstract: Advanced cutaneous squamous cell carcinoma (cSCC) is treated with chemotherapy and/or radiotherapy, but these typically fail to achieve satisfactory clinical outcomes. There have been no preclinical studies to evaluate the effectiveness of eribulin against cSCC. Here, we examine the effects of eribulin using cSCC cell lines and a novel cSCC patient-derived xenograft (PDX) model. In the cSCC cell lines (A431 and DJM-1 cells), eribulin was found to inhibit tumor cell proliferation in vitro as assessed by cell AT… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The lymph node metastasis from a 69‐year old Japanese male with a history of smoking was subcutaneously implanted into female NOD/ShiJic‐ scid Jcl mice, and subsequent tumours transplanted into further generations of mice. This model demonstrated that 1.5 mg/kg/week administration of the chemotherapeutic eribulin was as effective as the clinically‐utilised cisplatin in suppressing cSCC tumour growth 32 . Importantly, the PDX tumours and resultant primary cell lines retained key driver mutations observed in the patient's tumours, including those in tumour suppressors TP53 and ARID2 .…”
Section: Existing Patient‐derived Models Of Metastatic Csccmentioning
confidence: 88%
See 4 more Smart Citations
“…The lymph node metastasis from a 69‐year old Japanese male with a history of smoking was subcutaneously implanted into female NOD/ShiJic‐ scid Jcl mice, and subsequent tumours transplanted into further generations of mice. This model demonstrated that 1.5 mg/kg/week administration of the chemotherapeutic eribulin was as effective as the clinically‐utilised cisplatin in suppressing cSCC tumour growth 32 . Importantly, the PDX tumours and resultant primary cell lines retained key driver mutations observed in the patient's tumours, including those in tumour suppressors TP53 and ARID2 .…”
Section: Existing Patient‐derived Models Of Metastatic Csccmentioning
confidence: 88%
“…This model demonstrated that 1.5 mg/kg/week administration of the chemotherapeutic eribulin was as effective as the clinically-utilised cisplatin in suppressing cSCC tumour growth. 32 Importantly, the PDX tumours and resultant primary cell lines retained key driver mutations observed in the patient's tumours, including those in tumour suppressors TP53 and ARID2.…”
Section: E Xis Ting Patient-derived Model S Of Me Ta S Tatic C Sccmentioning
confidence: 98%
See 3 more Smart Citations